In Exercises 19 and 20 , assume that \( \angle \boldsymbol{A} \) is supplementary to \( \angle \boldsymbol{B} \) and complementary to \( \angle \boldsymbol{C} \). Determine \( \boldsymbol{m} \angle \mathbf{A}, \boldsymbol{m} \angle \boldsymbol{B} \), and \( \boldsymbol{m} \angle \boldsymbol{C} \). \( \begin{array}{c}\text { 157 } \\ \text { 19. } m \angle A=(x+10)^{\circ}, m \angle B=(12 x+1)^{\circ}, m \angle C=(5 x+2)^{\circ} \\ \text { 20. } m \angle A=(2.5 x+17)^{\circ}, m \angle B=(21 x-25)^{\circ} . m \angle C=(8 x-11)^{\circ} \\ 33.25\end{array} 111.5 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To tackle this problem, we need to set up some equations based on the relationships between the angles. Since angle \(A\) is supplementary to angle \(B\), we can express that as: \[ m\angle A + m\angle B = 180^\circ \] Additionally, since angle \(A\) is complementary to angle \(C\): \[ m\angle A + m\angle C = 90^\circ \] We can substitute the expressions given for \(m\angle A\), \(m\angle B\), and \(m\angle C\) into these equations. ### For Exercise 19: 1. Substitute the expressions: \[ (x + 10) + (12x + 1) = 180 \] Simplifying gives: \[ 13x + 11 = 180 \implies 13x = 169 \implies x = 13 \] 2. Now substitute \(x = 13\) back into the angle expressions: - \(m\angle A = 13 + 10 = 23^\circ\) - \(m\angle B = 12(13) + 1 = 157^\circ\) - \(m\angle C = 5(13) + 2 = 67^\circ\) ### For Exercise 20: 1. Using the same approach, set up the equations: \[ (2.5x + 17) + (21x - 25) = 180 \] Simplifying gives: \[ 23.5x - 8 = 180 \implies 23.5x = 188 \implies x \approx 8 \] 2. Substitute \(x \approx 8\) back into the expressions: - \(m\angle A = 2.5(8) + 17 = 25^\circ\) - \(m\angle B = 21(8) - 25 = 143^\circ\) - \(m\angle C = 8(8) - 11 = 53^\circ\) This brings us to the final measures of angles. There you go, angles \(A\), \(B\), and \(C\) are now all figured out!